1993
DOI: 10.1126/science.8484124
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Kinase-Stimulated Guanine Nucleotide Exchange Activity of Vav in T Cell Activation

Abstract: The hematopoietically expressed product of the vav proto-oncogene, Vav, shared homology with guanine nucleotide releasing factors (GRFs) [also called guanosine diphosphate-dissociation stimulators (GDSs)] that activate Ras-related small guanosine triphosphate (GTP)-binding proteins. Human T cell lysates or Vav immunoprecipitates possessed GRF activity that increased after T cell antigen receptor (TCR)-CD3 triggering; an in vitro-translated Vav fragment that contained the putative GRF domain was also active. Va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
181
1

Year Published

1993
1993
2000
2000

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 276 publications
(183 citation statements)
references
References 43 publications
1
181
1
Order By: Relevance
“…Indeed recent data have shown Vav can function as a GEF for Rac-1 in vitro and in vivo, leading to activation of the JNK/Jun signal transduction pathway (Crespo et al 1997). Some data, however, indicate that Vav may also associate and/or activate Ras GEFs during activation of the T-cell receptor and immunoglobulin (Gulbins et al 1993, 1994c, Clevenger et al 1995b. Finally, in the carboxy terminus of Vav reside two SH2 and one SH3 domains, with striking overall homology to the signal transduction adaptor protein Grb-2.…”
Section: Mediators Of Prl-induced Lymphocyte Proliferation -Vavmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed recent data have shown Vav can function as a GEF for Rac-1 in vitro and in vivo, leading to activation of the JNK/Jun signal transduction pathway (Crespo et al 1997). Some data, however, indicate that Vav may also associate and/or activate Ras GEFs during activation of the T-cell receptor and immunoglobulin (Gulbins et al 1993, 1994c, Clevenger et al 1995b. Finally, in the carboxy terminus of Vav reside two SH2 and one SH3 domains, with striking overall homology to the signal transduction adaptor protein Grb-2.…”
Section: Mediators Of Prl-induced Lymphocyte Proliferation -Vavmentioning
confidence: 99%
“…Marked variations in the expression of Vav mRNA and protein were observed in developing thymic T-lymphocyte populations (Bustelo et al 1993), suggesting that the regulation of this protein may be important during the development and expansion of T cells. The phosphorylation of Vav has been observed after stimulation of the T-cell receptor (Gulbins et al 1993), membrane immunoglobulin (Gulbins et al 1994c), Fc receptor (Margolis et al 1992), interferon receptor (Platanias & Sweet 1994), c-kit (Alai et al 1992), PRLr (Clevenger et al 1995b), and the receptors for IL-1 (Gulbins et al 1994a) and -2 (Evans et al 1993). Antisense experiments have revealed that the inhibition of Vav expression in embryonic stem cells prevents their in vitro differentiation into mature hematopoietic elements (Wulf et al 1993).…”
Section: Mediators Of Prl-induced Lymphocyte Proliferation -Vavmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the numerous PTK substrate proteins is the Vav1 proto-oncogene product (Gulbins et al, 1993). This 95 kDa protein displays a wide variety of structural motifs including a N-terminal calponin homology (CH) domain, an acidic domain (AD), a Dbl-homology (DH) domain, a putative bipartite nuclear localization signal (NLS), a pleckstrin homology (PH) domain, a cysteine-rich domain (CR) and one SH2-domain anked by two SH3 domains (Romero and Fischer, 1996).…”
Section: Introductionmentioning
confidence: 99%